Pengembangan Media Monopoli Untuk Meningkatkan Hasil Belajar IPAS Peserta Didik Kelas IV Sekolah Dasar - Widiawati, Risma; Putra, Galih Mahardika Christian (Universitas Muria Kudus, 2025)
This research is motivated by the problem of student learning outcomes in class IV IPAS subjects that are less than optimal. The purpose of the development of Monopoly media for buying and selling activities is to improve the learning outcomes of grade IV elementary school students. The research method used is Research and Development (RD) with the ADDIE development model. The subjects of this study were students at SD Negeri 2 Sidoharjo grade IV, with a total of 27 students. Data collection techniques applied, namely non-participant structured observation, unstructured or open interviews, documentation, questionnaires, and tess. The results of product validation on media experts amounted to 98.6% and on material experts 83.3%. Normality test obtained Sig. 0.541 on the pretest and Sig. 0.625 on the posttest. Then for the large scale, the results obtained Sig. 0.356 on the pretest and Sig. 0.089 on the posttest. The small scale t-test showed a result of 0.001 and the large scale showed a result of 0.000. The results of the N-Gain Test on a small scale amounted to 0.7019 with high criteria and a large scale of 0.7182 with high criteria. This study can be concluded that the Monopoly of Buying and Selling Activities media is feasible and effective for improving student learning outcomes.